Intensifying the particle deposition from a colloidal solution for the purpose of liquid purification: Comparison of deposition mechanisms and rates; Powder Technology; Vol. 434 - Misyura S. Ya. Sergey Yakovlevich; Egorov R. I. Roman Igorevich; Morozov V. S. Vyacheslav Sergeevich; Zaitsev A. S. Aleksandr Sergeevich (2024, 2024)
Title screen